Against the unification of the behavioral sciences - Clarke, S (2007)
The contemporary behavioral sciences are disunified and could not easily become unified, as they operate with incompatible explanatory models. According to Gintis, tolerance of this situation is "scandalous" (sect. 12). I defend the ordinary behavioral scientist's lack of commitment to a unifying explanatory model and identify several reasons why the behavioral sciences should remain disunified for the foreseeable future. © 2007 Cambridge University Press.